2012
DOI: 10.1111/j.1468-2362.2012.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Episodes of Large Capital Inflows, Banking and Currency Crises, and Sudden Stops

Abstract: This paper empirically investigates the relationship between surges in capital inflows and the probability of subsequent banking, currency and balance‐of‐payment crises. Using a panel of developed and emerging economies from 1970 to 2007, it shows that a large capital inflow episode increases substantially the probability of having a banking or a currency crisis in the two following years. The effect is especially large for the case of balance‐of‐payment crises. The paper also finds that the effect of large ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 74 publications
3
50
0
4
Order By: Relevance
“…The study of FDI surges and stops to developing countries is warranted since FDI volatility has been associated with declining long-run economic growth (Lensink and Morrissey 2006). There is also the long-standing concern that sudden stops and surges in foreign capital flows might contribute to and arise as a result of macroeconomic volatility (Calvo et al 2006) and crises (Reinhart and Reinhart 2009;Furceri et al 2012) as well as complicate macroeconomic management in developing economies. Abiad et al (2011) and Cowan and Raddatz (2011), for instance, point to a connection between sudden stops and credit market imperfections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of FDI surges and stops to developing countries is warranted since FDI volatility has been associated with declining long-run economic growth (Lensink and Morrissey 2006). There is also the long-standing concern that sudden stops and surges in foreign capital flows might contribute to and arise as a result of macroeconomic volatility (Calvo et al 2006) and crises (Reinhart and Reinhart 2009;Furceri et al 2012) as well as complicate macroeconomic management in developing economies. Abiad et al (2011) and Cowan and Raddatz (2011), for instance, point to a connection between sudden stops and credit market imperfections.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies compare different types of financial flow events (e.g., Sula 2010;Cardarelli et al 2010;Agosin and Huaita 2012;Forbes and Warnock 2012;Furceri et al 2012;Ghosh et al 2012), but to our knowledge, none looks separately at the incidence and determinants of GF-led and M&A-led stops and surges in FDI flows to the developing world. The distinction is important for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have used a probit model to estimate the probability of currency crises or currency crashes (Eichengreen et al 1996: Frankel andBerg and Pattillo 1999;Kruger et al 2000;Komulainen and Lukkarila 2003;Frankel 2005;Licchetta 2011;Furceri et al 2012;Zhao et al 2014). 6 Before examining the empirical literature, it is worth distinguishing between "currency crises" and "currency crashes" because these are two different concepts that are frequently confused.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Frankel (2005) also found that higher import coverage of international reserves is associated with a lower probability of currency crashes. Moreover, according to the probit estimation results presented by Furceri et al (2012), international reserves and short-term interest rates are relevant for the probability of currency crashes. Zhao et al (2014) found that real exchange rate overvaluation and international reserves are important determinants of currency crashes for fixed exchange rate regimes, whereas credit growth is important for floating regimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While Vermuelen and de Haan (2014) found that financial development was inversely linked to the issuance of equity, Faria et al (2007) reported that financial reform contributed to an increase in the share of equity on a country's external balance sheet. When FDI and portfolio equity are treated separately, several authors (Lane and Milesi-Ferretti 2001a, Wei 2006, Daude and Fratzscher 2008, Furceri and Guichard 2012 find that financial development leads to the issuance of more portfolio equity. We also excluded the countries that became market economies in the wake of the dissolution of the Soviet Union, as their financial data commence in the 1990s and do not include the earlier period when debt liabilities were more common.…”
mentioning
confidence: 99%